Então, para aonde vamos, Agamben ? Uma análise crítico-neoretórico-neopragmática sobre o discurso de Direitos Humanos no projeto Homo Sacer - Luna, Moisés Saraiva de (2024)
The main research objective of this thesis was to conduct an analysis of the Human Rights discourse in Giorgio Agamben, having as its primary source the collection of nine works and four volumes called Homo Sacer, extending outside of it when necessary. We go through a specific epistemological approach, using the contributions of the new rhetoric of Chaïm Perelman and Lucie Olbrechts-Tyteca, the neopragmatism of Richard Rorty and critical discourse analysis, mainly outlined by Norman Fairclough. We justify the research by considering the international dissemination of its theories undeniable, the high level of criticism presented and the importance of Human Rights in contemporary times. The method used was developed by crossing the three theoretical influences, incorporating only parts of each theory, in the form of its own study instrument, as well as being derived from qualitative, deductive research, with a historical approach. The central question to be answered was: Considering the plurality of human cultures, the historical processes of domination and exclusion, the agambenian argumentative construction found in the HS project, critical of the standard discourse on Human Rights, can, if appropriated by these groups, be considered a better redescription of reality, with a view to reducing human suffering and cruelty? The hypothesis was elaborated as follows: Despite the undeniable contributions of his thought to the advancement of criticism of liberalism, the Rule of Law and Human Rights, in short, the social form of the West, it does not seem to be a better redescription of reality, even if it is very convincing for those who read his texts. To achieve the central objective, we proceeded by exposing the theoretical-philosophical assumptions of the thesis and the theoretical framework, as a context for understanding his speech on Human Rights. Next, we elaborate the strict discourse on Human Rights, present especially in the first two books of the collection and expand the connections between them and the other works, through the interconnections between the strict discourse and an expanded discourse on Human Rights. We delimit the epistemic-methodological confluences and divergences of New Rhetoric, Neopragmatism and Critical Discourse Analysis for the elaboration of the analytical set and, finally, we evaluate, through critical-neorhetorical-neopragmatic analysis, the possibility of implementing the agambenian speech on the Human Rights, based on the difficulties and challenges presented to it. Our results partially confirm the hypothesis, suggesting that its proposal may be feasible, as long as it resolves conceptual problems, reduces its degree of abstraction and incorporates, through practice and theory, the contributions of intersectionality and decoloniality, both outside your field of study.